Análisis de los proyectos y actores transfronterizos España-Francia en el período 2007-2013 - Feliu Torrent, Jaume; Berzi, Matteo; Vicente Rufi, Joan; Castañer Vivas, Margarida; Llussà Torra, Rafael (Geographicalia, 2014)
This research is part of the study of the economic and territorial developments that take place in the border areas between France and Spain. Specifically, we study the characteristics of cross-border cooperation projects INTERREG IV-A developed during the 2007-2013 period. These projects are taken as examples of the dynamics produced by stakeholders and development projects between the two sides of the border. To meet this objective, a database system has been designed to dump the information of the projects. The information is further processed in order to extract quantitative results and cartographic images, using the capabilities of geographic information systems.